REFORMASI AL-QUR’AN DALAM HUKUM PERCERAIAN: Kajian Antropologi Hukum Islam - Sodiqin, Ali (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
Islamic law, including divorce law, has a dialectical relationship withthe traditions of Arab society as its first recipient. Therefore, explainingIslamic law must consider the historical and anthropological situationArab’s community in 7th century AD. The social structure, politics,and economics of Arab society at that time had a strong influence for theenforcement of Islamic law. Anthropologically, the differences of the rightsand obligations between husband and wife in the law of divorce wasinseparable from the dynamics of a growing cultural community. Islamiclaw governs the conduct of divorce as it adjusts to the social conditionsof Arab society at the time. So the divorce legal texts in the Quran mustbe explained by the socio-cultural context of the recipient. When thesocio-cultural is change, change of the law of divorce is permissible. Thesubstance of the law of divorce in Islam is to place the divorced parties(husband and wife) to be equal, ie, have the same rights and obligations.The difference in the rights and obligations of husband and wife foundin texts of Islamic law due to the efforts of adoption, adaptation, andintegration of the revelation of the Qur’an with the traditions of Arabsociety. In the context of socio-cultural system now, can be a mediumfor constructing the divorce laws in Islamic law towards social justice.